2019
DOI: 10.1097/md.0000000000014048
|View full text |Cite
|
Sign up to set email alerts
|

The influence of obesity, smoking, and serum follicular stimulating hormone in azoospermic patients on testicular sperm extraction-intra cytoplasmic sperm injection outcomes

Abstract: To examine the effect of serum follicle-stimulating hormone (sFSH) level, body-mass index (BMI) and smoking on Testicular Sperm Extraction–Intracytoplasmic Sperm Injection (TESE–ICSI), and pregnancy outcomes.In this retrospective study, data were extracted from files of 52 azoospermic men who underwent TESE and in-vitro fertilization (IVF)-ICSI in our IVF unit. Demographic information, treatment cycle follow-up and pregnancy outcomes were collected.Fifty-two patients underwent 79 TESE due to azoospermia in 143… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…This study has shown that an increase in age increases fertility, though some studies have been demonstrated that increasing paternal age is associated with decreased fertility rate (Shrem et al, 2019). Contrasting results of this study might be due to the fact that males aged 40–49 years found to be a 52% decrease in normal sperm motility, while it was markedly reduced by 79% at 50 years or older (Mariappen et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…This study has shown that an increase in age increases fertility, though some studies have been demonstrated that increasing paternal age is associated with decreased fertility rate (Shrem et al, 2019). Contrasting results of this study might be due to the fact that males aged 40–49 years found to be a 52% decrease in normal sperm motility, while it was markedly reduced by 79% at 50 years or older (Mariappen et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…In agreement with our finding, Wu et al [20] reported no correlation between paternal age and clinical pregnancy rate. In contrast, Shrem et al [21] had shown that paternal age above 37 years was significantly adversely correlated with clinical pregnancy. Besides, serum FSH levels of the females in the easy NOA group were significantly lower and had shown a significant correlation with clinical pregnancy than those in the difficult NOA group which could be explained by the fact that patients with elevated FSH levels are associated with decline in the quantity of the ovarian reserve with subsequent reduced pregnancy and live birth rates [22] .…”
Section: Discussionmentioning
confidence: 88%
“…In the same line, a study conducted by Guler et al [27] stated that testicular histopathology did not influence pregnancy rate in patients with NOA. Furthermore, Shrem et al [21] did not find any correlation between male FSH level and clinical pregnancy. On the contrary, a study conducted by Zitzmann et al [28] had shown that an FSH cutoff of 20 IU predicted pregnancy.…”
Section: Discussionmentioning
confidence: 89%
“…There are also other mechanisms of reduced fertility in males that are associated with obesity, including inflammation that has been shown to reduce sperm quality and motility, reactive oxygen species that may cause, D.N.A. ; protein, and membrane damage in sperm cells, as well as epigenetic changes that contribute to subfertility [16,94,95,96,97,98,99,100]. These effects potentially contribute to long term subfertility for adolescent males with obesity who continue to have excess adipose tissue and experience hypogonadism in adulthood.…”
Section: Discussionmentioning
confidence: 99%